2020
DOI: 10.1101/2020.09.23.309898
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A joint reaction coordinate for computing the free energy landscape of pore nucleation and pore expansion in lipid membranes

Abstract: Topological transitions of membranes, such as pore formation or membrane fusion, play key roles in biology, biotechnology, and in medical applications. Calculating the related free energy landscapes has been complicated by the fact that such processes involve a sequence of transitions along highly distinct directions in conformational space, making it difficult to define good reaction coordinates (RCs) for the overall process. In this study, we present a new RC capable of driving both pore nucleation and pore … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
(89 reference statements)
1
1
0
Order By: Relevance
“…A previous study also reported that for 20 independent, unbiased simulations of DMPC pores, zero closed within 500 ns ( 17 ), which suggests that the closure barrier is substantial. The energy landscape suggests that applied surface tension should increase the radius of this metastable defect, in accordance with a Litster type energy model, as has been reported in other studies ( 13 , 49 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A previous study also reported that for 20 independent, unbiased simulations of DMPC pores, zero closed within 500 ns ( 17 ), which suggests that the closure barrier is substantial. The energy landscape suggests that applied surface tension should increase the radius of this metastable defect, in accordance with a Litster type energy model, as has been reported in other studies ( 13 , 49 ).…”
Section: Resultssupporting
confidence: 89%
“…This value has not been reported previously because the full PMF, including the entire metastable basin, was not resolved with a single RC. Just recently, however, this result has been confirmed, independently ( 49 ), using an empirical RC that combines the slab scheme of ( 14 ) with a lateral expansion RC. A previous study also reported that for 20 independent, unbiased simulations of DMPC pores, zero closed within 500 ns ( 17 ), which suggests that the closure barrier is substantial.…”
Section: Resultsmentioning
confidence: 85%